A Register of Early Modern Slovenian Manuscripts - Matija Ogrin; Jan Jona Javoršek; Tomaž Erjavec (Journal of the Text Encoding Initiative)
This paper presents the Register of Early Modern Slovenian Manuscripts, which includes manuscripts from the 17th and 18th centuries that have been overlooked by scholars focused on printed books from the same era. The Register attempts to address this gap in Slovenian manuscript studies by describing these unknown and forgotten early modern manuscripts with facsimiles, an index of basic manuscript citations, and a bibliography containing publications where these manuscripts are mentioned. It is encoded in TEI P5 using the manuscript description module and available via a web interface. The paper discusses the specifics of early modern manuscripts, explains the structure and encoding of the Register (especially encoding of temporal and geographic data), and presents the portal built using the Fedora Commons repository software that allows the user to browse and search manuscripts and export data in TEI format, and that enables metadata harvesting.